Religious Moderation in Risalah Islam Berkemajuan: A Perspective from Karl Mannheim’s Sociology of Knowledge - Syafi'i, Ali Ridho; Ghorbanali Karimzadeh Gharamaleki (Faculty of Ushuluddin and Philosophy, 2023)
This article explores the concept of religious moderation as articulated within the framework of Risalah Islam Berkemajuan (Progressive Islamic Mission), a key ideological formulation of Muhammadiyah that emphasizes rationality, tolerance, social ethics, and engagement with modernity. The study aims to understand how this framework constructs religious moderation not merely as a theological posture, but also as a socially embedded discourse shaped by historical and epistemological contexts. To deepen the analysis, Karl Mannheim’s theory of sociology of knowledge is employed as a theoretical lens. Mannheim’s insight into the relationship between thought and social location allows for a critical reading of how Muhammadiyah’s Risalah Islam Berkemajuan responds to socio-political challenges, especially in pluralistic societies. This article argues that religious moderation in this context functions both as a normative ideal and as a strategic socio-religious construct that reflects the dynamic interplay between ideology and social structure. Through this approach, the study highlights the epistemic foundations and sociological relevance of religious moderation in contemporary Islamic discourse.